The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1113/ep086994
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen therapy improves cerebral oxygen delivery and neurovascular function in hypoxaemic chronic obstructive pulmonary disease patients

Abstract: We investigated the role of hypoxaemia in cerebral blood flow (CBF), oxygen delivery (CDO ) and neurovascular coupling (coupling of CBF to neural activity; NVC) in hypoxaemic chronic obstructive pulmonary disease (COPD) patients (n = 14). Resting CBF (duplex ultrasound), peripheral oxyhaemoglobin saturation (SpO2; pulse-oximetry) and NVC (transcranial Doppler) were assessed before and after a 20 min wash-in of supplemental oxygen (∼3 l min ). The peripheral oxyhaemoglobin saturation increased from 91.0 ± 3.3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Alternatively, it is also possible that ALFF does not change so sensitively to the increase in PaO 2 in a relatively lower range in COPD patients. A recent study claims that the cerebral vasculature of COPD patients is insensitive to low‐flow oxygen delivery because of the unaltered CBF (Hoiland et al, ). There are some reports indicating that long‐term oxygen treatment will not improve the survival of COPD patients with moderate resting hypoxemia (Chaouat et al, ; Gorecka, Gorzelak, Sliwinski, Tobiasz, & Zielinski, ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is also possible that ALFF does not change so sensitively to the increase in PaO 2 in a relatively lower range in COPD patients. A recent study claims that the cerebral vasculature of COPD patients is insensitive to low‐flow oxygen delivery because of the unaltered CBF (Hoiland et al, ). There are some reports indicating that long‐term oxygen treatment will not improve the survival of COPD patients with moderate resting hypoxemia (Chaouat et al, ; Gorecka, Gorzelak, Sliwinski, Tobiasz, & Zielinski, ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only a small proportion of patients received HNPPV (3% vs. 10.5% vs. 1.0% in teaching hospital vs. second-tier hospital vs. community hospital group), whereas the proportions of patients with very severe air ow limitation (GOLD 4) were 8.9%, 6.9% and 2.0% in the 3 tiers of hospitals, respectively. A meta-analysis including 21 RCTs and 12 observational studies evaluating 51 085 patients showed that home bilevel positive airway pressure and noninvasive home mechanical ventilators were all signi cantly bene cial to COPD patients with hypercapnia 15,16 . Murphy's study 17 showed that among patients with persistent hypercapnia following an AE of COPD, adding home noninvasive ventilation to home oxygen therapy prolonged the time to readmission or death within 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, oxygen therapy appears beneficial for patients with COPD. On the contrary, oxygen therapy did not alter volumetric global CBF (Hoiland et al., ), suggesting that the cerebral vasculature has a low sensitivity to the acute normalization of SnormalpO2. From these results, it can be suspected that the contribution of CBF regulation to COPD‐induced cerebrovascular disease or brain dysfunction is likely to be minimal.…”
mentioning
confidence: 96%
“…Given this background, Hoiland et al. () have reported, in this issue of Experimental Physiology , the effects of oxygen therapy on cerebral oxygen delivery and neurovascular function in patients with COPD. The authors demonstrated that oxygen therapy improved cerebral oxygen delivery by increasing peripheral oxyhaemoglobin saturation (SnormalpO2) and enhanced neurovascular function in patients with COPD.…”
mentioning
confidence: 99%
See 1 more Smart Citation